Women’s Empowerment, Agency and Self-Determination in Afrobeats Music Videos: A Multimodal Critical Discourse Analysis - Rens, Simphiwe Emmanuel (Frontiers in Sociology, 2021)
Stemming from a broader PhD project, this article argues that neoliberal post-feminist cultural sensibilities – entrenched in contemporary popular culture – about empowered, agentic and self-determining women, are regressive for the feminist advancement of gender-relational equality in the African context. To arrive at this conclusion, the central aim was to elucidate whether the gender-performative representations prioritised in the multimodal discourses of Afrobeats music videos are implicated in post-feminist sensibilities and if so, in what ways and to what effect? Given the continent’s richly diverse, yet largely heteropatriarchal, sociocultural formations, I argue that ideas about empowered, agentic and self-determining (black) African women are – based on the limited purview offered through the multimodal discourses of a small corpus of Afrobeats music videos – no more than sociocultural façades as opposed to gender-relational realities in our context. The article relied on a multimodal critical discourse analysis of a total of nine music videos drawn from the PhD project’s larger corpus of 25 Afrobeats music videos, their accompanying song lyrics, as well as a selection of YouTube viewer comments extracted from the nine analysed music videos. In critically exploring the gender-relational depictions prioritised in the analysed music videos, I argue for the consideration of what I am coining ‘misogyrom’; a gender-relational cultural sensibility which, in tandem with a post-feminist sensibility partly undergirding the multimodal discourses of these music videos, effectively veil this popular musical genre’s evidently sexist and misogynistic undertones that subvert potentialities of empowered, agentic and self-determining black African women.